Airway management evolution - in a search for an ideal extraglottic airway device - Michálek, Pavel; Miller, Donald M (Prague medical report, 2014)
Extraglottic airway devices (EADs) are commonly used equipment for airway maintenance during elective procedures under general anaesthesia. They may be used also in other indications such as conduit for tracheal intubation or rescue airway device in prehospital medicine. Current classifications of the EADs lack systematic approach and therefore classification according to the sealing sites and sealing mechanisms is suggested in this review article. Modern EADs are disposable, latex-free devices made of plastic materials most commonly from polyvinylchloride (PVC). The bowl of uncuffed sealers is manufactured from different materials such as thermoplastic elastomers or ethylene-vinyl-acetate co-polymer. EADs create various physical forces exerted on the adjacent tissues which may contribute to different sealing characteristic of particular device or to variable incidence of postoperative complications. Desired features of an ideal EAD involve easy insertion, high insertion success rate even by inexperienced users, protection against aspiration of gastric contents and low incidence of postoperative complications such as sore throat, hoarseness, cough or swallowing difficulties.
Keywords: zajištění dýchacích cest; Anesthesia, General; Airway Management; celková anestezie; Postoperative Complications; laryngální masky; lidé; pooperační komplikace; Humans; Laryngeal Masks; Equipment Design; design vybavení